Association of paramagnetic rim lesions and retinal layer thickness in patients with multiple sclerosis. (March 2023) - Krajnc, Nik; Dal-Bianco, Assunta; Leutmezer, Fritz; Kasprian, Gregor; Pemp, Berthold; Kornek, Barbara; Berger, Thomas; Rommer, Paulus Stefan; Hametner, Simon; Lassmann, Hans; Bsteh, Gabriel
Background: Paramagnetic rim lesions (PRLs) are chronic active lesions associated with a more severe disease course in multiple sclerosis (MS). Retinal layer thinning measured by optical coherence tomography (OCT) is a biomarker of neuroaxonal damage associated with disability progression in MS. Objective: We aimed to determine a potential association between OCT parameters (peripapillary retinal nerve fiber layer (pRNFL) ganglion cell-inner plexiform layer (GCIPL), inner nuclear layer (INL) thickness), and PRLs in patients with MS (pwMS). Methods: In this cross-sectional retrospective study, we included pwMS with both 3T brain MRI and an OCT scan. Regression models were calculated with OCT parameters (pRNFL, GCIPL, INL) as dependent variables, and the number of PRLs as an independent variable adjusted for covariates. Results: We analyzed data from 107 pwMS (mean age 34.7 years (SD 10.9), 64.5% female, median disease duration 6 years (IQR 1–13), median EDSS 1.5 (range 0–6.5)). Higher number of PRLs was associated with lower pRNFL (β = −0.18; 95% CI −0.98, −0.03; p  = 0.038) and GCIPL thickness (β = −0.21; 95% CI −0.58, −0.02; p  = 0.039). Conclusion: The association between higher number of PRLs and lower pRNFL and GCIPL thicknesses provides additional evidence that pwMS with PRLs are affected by a more pronounced neurodegenerative process.